(untitled) (Orthodontic Journal of Nepal, 2013)
Introduction: Gingival recession is the location of marginal periodontal tissues apical to the cemento-enamel junction, which can lead to many clinical problems. The prevalence, extension and severity of gingival recession present considerable differences among various study populations. Objective: To assess the prevalence, extension and severity of gingival recession among rural Nepalese adults. Materials & Method: The study was performed on 246 adult dentate rural patients above 20 years of age having at least 24 natural teeth. The prevalence, extension and severity of gingival recession were assessed by a single examiner using William’s graduated periodontal probe. Type and severity of gingival recession was recorded by using Miller’s criteria of apico-coronal height of recession defects. Result: Gingival recession was present in 65.44 % of the total study sample and mean number of teeth with gingival recession was 9.77. The prevalence of gingival recession was 41.37%, 58.90%, 77.41% and 86.79% in age groups of 20-29 years, 30-39 years, 40-49 years and ≥ 50 years respectively. In younger age groups Class I gingival recession was more prevalent whereas Class III and Class IV gingival recession was more prevalent in older age groups. Mandibular central incisors were the teeth most frequently affected by gingival recession (7.3%). Conclusion: 9.64% of teeth were affected by severe form of gingival recession at the age group 20-29 years as compared to 48.09 % at the age groups more than 50 years. High prevalence of gingival recession in adult subjects provides information about the importance of diagnosis and knowledge on these pathological gingival changes. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9281 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 41-46